PEMBERDAYAAN MASYARAKAT BERBASIS PEMANFAATAN LAHAN KOSONG MENJADI TAMAN KERANGGAN SALAWI - Khasiatillah Khasiatillah; Hairi Rahman; Muhammad Alfi Alfariz; Ulva Ayu Lestari; Noorhayati Noorhayati; Iin Muti Atuz Zahro; Ersa Chandra Ningrum; Al Muja Hidah; Elsya Dwiyanti; Ardika Ramadhan (LP2M Universitas Hasanuddin, 2024)
There is still a lot of empty land in Tanjung Pinang Village which is only overgrown with shrubs and has not been utilized optimally, which will impact on the emergence of various problems, one of which is becoming a nest for dangerous animals such as snakes. With an area of ​​around 4,400 hectares with moderate rainfall intensity, the village of Tanjung Pinang has considerable natural resource potential. However, the limitations of the local community to able to take advantage of the existing potential have resulted in many vacant lands not being used. This service activity is carried out with the intention that the community can utilize vacant land as open space such as a relaxing garden which incidentally does not yet exist in the area. The presence of a park can be an element of refreshment and entertainment after residents are tired of their activities. In addition, parks also play an important role in building intelligence in children. The method used in this community service activity is participatory. The result of this program is the creation of a relaxing garden in the Tanjung Pinang area which is named Taman Keranggan Salawi. The stages in making the Keranggan Salawi garden consist of the planning, counseling, and program implementation stages. From the activity of using vacant land to become the Salawi Shellfish Park which was made by KKN Group 83 students at IAIN Palangka Raya in 2022, it is hoped that it will become a relaxing park as well as a recreation area that will provide a beautiful, attractive, comfortable, healthy and fun environment. The results of this community service activity have an impact on increasing public understanding of the importance of managing other productive land that is not used properly with the mastery level of the participants in this activity related to procedures for managing vacant land of ≥90%. — Masih banyaknya lahan kosong di Desa Tanjung Pinang yang hanya ditumbuhi semak belukar dan belum dimanfaatkan secara optimal, akan berdampak pada munculnya berbagai permasalahan salah satunya menjadi sarang hewan berbahaya seperti ular. Dengan luas wilayahnya sekitar 4.400 Hadengan inrtensitas curah hujan sedang menjadikan desa Tanjung Pinang ini memiliki potensi sumber daya alam yang cukup besar. Namun keterbatasan dari masyarakat setempat untuk bisa memanfaatkan potensi yang ada menyebabkan banyaknya lahan-lahan yang kosong yang tidak difungsikan. Kegiatan pengabdian ini dilakukan dengan maksud agar masyarakat dapat memanfaatkan lahan kosong sebagai ruang terbuka seperti taman santai yang notabene belum ada di kawasan tersebut. Kehadiran taman bisa menjadi elemen menyegarkan dan hiburan setelah warga lelah beraktivitas. Selain itu, taman juga berperan penting dalam membangun kecerdasan pada anak. Metode yang digunakan dalam kegiatan pengabdian masyarakat ini adalah Partisipatori. Hasil dari program ini adalah pembuatan taman santai di kawasan Tanjung Pinang yang diberi nama Taman Keranggan Salawi. Tahapan dalam pembuatan taman Keranggan Salawi terdiri dari tahap perencanaan, penyuluhan, dan pelaksanaan program. Dari kegiatan pemanfaatan lahan kosong menjadi Taman Keranggan Salawi yang dibuat oleh mahasiswa KKN Kelompok 83 IAIN Palangka Raya pada tahun 2022 diharapkan dapat menjadi taman santai sekaligus tempat rekreasi yang akan memberikan lingkungan asri, menarik, nyaman, sehat serta menyenangkan. Hasil kegiatan pengabdian masyarakat ini berdampak pada meningkatnya pemahaman masyarakat tentang pentingnya mengelola lahan produktif lainnya yang tidak digunakan dengan baik dengan tingkat penguasaan peserta kegiatan ini terkait tata cara pengelolaan lahan kosong adalah ≥90%.